Dentofacial changes after anterior crossbite correction using a lingual arch with finger springs - Hsin-Chung Cheng; Mei-Ju Shih (Journal of Dental Sciences, 2017)
Background/purpose: Anterior crossbite correction is common in orthodontic treatment; however, few studies have discussed the change with cephalometric measurements. The purpose of this study was to evaluate the dentofacial changes in anterior crossbite correction by using an upper lingual arch with finger springs. Materials and methods: This retrospective study included 30 patients (13 female and 17 male). According to the number of crossbite teeth, the patients were divided into three groups. We used paired t test, Kruskal–Wallis test, Mann–Whitney U test, and multiple regression analysis to perform statistical analysis. Results: According to overall treatment changes, the dental changes included overjet increase, overbite decrease, upper incisor proclination, lower incisor retroclination and intrusion, upper molar distal tipping with extrusion, and lower molar intrusion. These dental changes resulted in clockwise mandibular rotation and lip position change. Anterior crossbite correction did not require increasing bite appliances. According to multiple regression analysis, the change in overjet was associated with the position of the upper and lower incisor crown tips. The mean rate of upper incisor movement in the horizontal direction was 2.5 mm/mo. The treatment duration exhibited no significant difference among the three groups. Conclusion: Lingual arch with finger springs was effective in anterior crossbite correction regardless of the number of crossbite teeth.